Z dokazi podprta storitev pregled uporabe zdravil v Sloveniji - Nabergoj Makovec, Urška (Farmacevtski vestnik, 2019)
Slovenia is one of the 14 European countries in which community pharmacies offer medicines use review service. The aim of this narrative review is to present current evidence on benefits of the service in Slovenia and to address challenges for the future development of the service. Results of the randomised controlled clinical study show medicines use review in Slovenia enhances adherence among patients with low level adherence. In addition, the study confirms service%s ability to identify high number of manifested drug related problems and around half is also partially or fully resolved. moreover, due to the service patients are less worried about adverse or long-term effects of their medicines. Better identification of patients with low adherence in practice should be addressed in the future, one of the possibilities is to create target patient groups for the service.
Keywords: koristi; Lekarne; pregled uporabe zdravil; sodelovanje pacientov pri zdravljenju z zdravili; tarčne skupine pacientov; z dokazi podprta lekarniška dejavnost; Zdravila